Możliwości wykorzystania odpadów jako surowców energetycznych w Polsce - Biernat, Krzysztof; Dziołak, Paulina Luiza; Samson-Bręk, Izabela (Studia Ecologiae et Bioethicae, 2011)
Status of municipal waste management in Poland requires decisive action in this regard. At present only a small percentage of wastes are utilized. In this state of affairs affects the low environmental awareness, lack of waste management plans in the municipalities, as well as the lack of installations for waste recovery and disposal. This article presents the most important legislation both at the European and national level on waste management. Discusses the prospects for the energy use of waste particularly with firing and co-firing waste technology with heat recovery at the same time.